Использование канонической формы функции отклика при оптимизации конструкций - Пылева, Татьяна Кузьминична (НТУ "ХПИ", 2017)
Предлагается методика выбора начальных точек оптимизации функции отклика второго порядка, повышающая экономичность классических методов оптимизации. Методика основана на преобразовании соответствующего полинома к канонической форме, определении центра симметрии исследуемой поверхности и анализе коэффициентов модели. Начальные точки оптимизации выбираются в зависимости от расположения центра симметрии исследуемой поверхности относительно области адекватности функции отклика. Приведены примеры использования методики.

Optimizing the design parameters of the technical systems in the process of their design is generally accepted prerequisite for achievement of high technical and economic indices of production. The place has the existence of a significant amount of research in this area. This explains the development and efficient algorithms for optimal solutions. The technique of selecting the starting points feature second-order response optimization. The technique improves the efficiency of classical optimization methods. The method is based on the conversion of the corresponding polynomials to canonical form; define the centre of symmetry of the studied surface and analysis of coefficients of the model. The starting points of optimization are chosen depending on the location of the centre of symmetry of the studied surface relative to the area of the adequacy of the response function. Examples of the use of the methodology are presented.
Keywords: полином; модель; экстремум функции; область адекватности; оптимизация; polynomial; model; extremum of the function; scope of adequacy; optimization